2007
DOI: 10.1348/135532506x147413
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationship between low empathy and self‐reported offending

Abstract: Purpose. This paper reports the results of a study comparing measures of cognitive and affective empathy to self‐reported offending in a group of adolescents. Methods. Data on self‐reported offending and empathy were collected from 720 UK adolescents (376 males, 344 females) in Year 10 (mean age = 14.8) using anonymous questionnaires administered in a classroom setting. The prevalence of self‐reported offending was found to be consistent with results of a national level study that employed a similar methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
89
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 50 publications
3
89
1
1
Order By: Relevance
“…For example, social aggression, a prominent feature of psychopathy, is more common in high testosterone-low cortisol individuals, rather than in all high-testosterone individuals indiscriminately (Terburg et al 2009). The results of our study suggest that lower empathy in high-testosterone/low-cortisol individuals may be a factor that contributes to the expression of their assertive or aggressive tendencies (Miller and Eisenberg 1988;Jolliffe and Farrington 2004;Jolliffe and Farrington 2007).…”
Section: Discussionmentioning
confidence: 65%
“…For example, social aggression, a prominent feature of psychopathy, is more common in high testosterone-low cortisol individuals, rather than in all high-testosterone individuals indiscriminately (Terburg et al 2009). The results of our study suggest that lower empathy in high-testosterone/low-cortisol individuals may be a factor that contributes to the expression of their assertive or aggressive tendencies (Miller and Eisenberg 1988;Jolliffe and Farrington 2004;Jolliffe and Farrington 2007).…”
Section: Discussionmentioning
confidence: 65%
“…Consistent with this separation of the affiliative and cognitive facets of empathy, bullies and other antisocial individuals are often found to be deficient in affective empathy [8,18,19,20]. Unsurprisingly, affective deficits are also found in people who fail to show remorse or concern for other people and their values, such as is shown with people with callous-unemotional traits [see 24].…”
mentioning
confidence: 91%
“…It has been suggested that empathic responsiveness inhibits aggressive behaviour because an empathic person is able to share in the emotions of distress of the victim [7]. Empathy deficits also characterize children who are violent and antisocial [8,18,19,20], but each of these studies highlights the need to measure specific types of empathy.…”
mentioning
confidence: 99%
“…Results were stronger for cognitive empathy (understanding of another's emotions) than for affective empathy (experience of another's emotions), although the relation between affective empathy and delinquency remains equivocal (Jolliffe & Farrington, 2007). This finding is of major importance, because empathy is thought to be a motivational base for moral development (Eisenberg & Eggum, 2009).…”
Section: Introductionmentioning
confidence: 99%